Burkina Faso : Report on the Observance of Standards and Codes-Fiscal Transparency Module. (IMF Staff Country Reports; Country Report ;, 2002)
This report assesses the Observance of Standards and Codes on Fiscal Transparency Module for Burkina Faso. Burkina Faso has made progress in recent years in increasing the level of fiscal transparency: the legislative basis has been strengthened; a medium-term expenditure framework has been implemented; an integrated financial management and information system is largely in place; and the preparation of program budgets will allow the budget to focus increasingly on government objectives. However, there are a number of areas where improvements are needed.